Family Financial Management Behavior in Housewives (A Phenomenological Review) - Nadhiroh, Umi; Mukhlis, Imam (PT FORMOSA CENDEKIA GLOBAL, 2023)
Financial management is a person's way of managing their finances, starting from planning, budget design, methods of saving funds, controlling expenses, to risk protection. The goal is to achieve economic stability in the future. This type of research is qualitative research with a phenomenological approach. Data collection techniques using participatory observation, non-participatory observation, interviews and documentation. The results of this research show that the behavior that occurs is that some of the informants have recorded their income and expenses every day, save regularly in the form of saving money, prepare emergency funds, and participate in social gatherings. They consider social gatherings to be part of saving. The most important management of family income is for consumption needs, then for children's school financing needs and social needs.